Large demographic shocks and small changes in the marriage market - Loren Brandt; Aloysius Siow; Carl Vogel (Institute for the Study of Labor (IZA), 2009)
This paper provides non-parametric estimates of the total effects of famine in China on marital behavior of famine affected cohorts in rural areas of Sichuan and Anhui. The reduced form estimates incorporate general equilibrium and heterogeneous treatment effects, two important components of equilibrium marital behavior. Next the paper uses a structural model of the marriage market to decomposed observed marital outcomes into quantity and quality effects. The structural estimates show that the famine reduced the marital attractiveness of the famine-born cohort. The conclusion is that the small observed changes in marriage rates of the famine born cohort are due to a significant decline in marital attractiveness.
Keywords: J12; 330; Marriage market; famine; Unterernährung; Ehe; Ländlicher Raum; Familienökonomik; China